2011
DOI: 10.1186/1471-2458-11-188
|View full text |Cite
|
Sign up to set email alerts
|

The views of young children in the UK about obesity, body size, shape and weight: a systematic review

Abstract: BackgroundThere are high levels of concern about childhood obesity, with obese children being at higher risk of poorer health both in the short and longer terms. Children's attitudes to, and beliefs about, their bodies have also raised concern. Children themselves have a stake in this debate; their perspectives on this issue can inform the ways in which interventions aim to work.This systematic review of qualitative and quantitative research aimed to explore the views of UK children about the meanings of obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 33 publications
(86 reference statements)
7
119
1
5
Order By: Relevance
“…These children's own friendship preferences for healthy weight or thin shaped characters over fat characters are in agreement with other studies in this age group (e.g., Musher-Eizenman et al, 2004) and in older children (Hill & Silver, 1995). The social rejection aspect of anti-fat bias is evident in the mere proximity literature above, in adolescent social network analyses (Strauss & Pollack, 2003), and evidence reviews of research with children of primary school age (Rees et al, 2011). Similarly, the cooccurrence of obesity and impaired social acceptance has been observed in the US Early Childhood Longitudinal Study when children were 9 to 11-years-old (Jackson & Cunningham, 2015).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These children's own friendship preferences for healthy weight or thin shaped characters over fat characters are in agreement with other studies in this age group (e.g., Musher-Eizenman et al, 2004) and in older children (Hill & Silver, 1995). The social rejection aspect of anti-fat bias is evident in the mere proximity literature above, in adolescent social network analyses (Strauss & Pollack, 2003), and evidence reviews of research with children of primary school age (Rees et al, 2011). Similarly, the cooccurrence of obesity and impaired social acceptance has been observed in the US Early Childhood Longitudinal Study when children were 9 to 11-years-old (Jackson & Cunningham, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…This contrasts with much clearer evidence of gender differences in older children and adolescents (Rees, Oliver, Woodman, & Thomas, 2011). Accordingly, investigating young children's responses to a female character drawn identically to the male character above (healthy weight, fat, in a wheelchair) was the main aim of the second study.…”
mentioning
confidence: 99%
“…Studies involving ethnic minorities in UK have shown increasing prevalence of obesity, greater risk of developing HTN, lower level of physical activity, higher mean total calorie intake, and altered perception to childhood obesity by the parents in south Asian population, and the situation is even worse in Bangladeshi childen. [41][42][43][44][45][46][47][48] Further research is needed in this field to elucidate the different aspects of childhood HTN in Bangladesh and to chalk-out plan to prevent adult HTN more efficiently.…”
Section: Hypertension In Childrenmentioning
confidence: 99%
“…(see [11]:483)). 2) Qualitative studies: Qualitative studies will be assessed using Harden's methodology [54] applied in Rees et al [55] and Pullin et al [37]. This assessment tool uses eight study validity criteria focusing on 1) study design and methods (rigour of sampling, data collection and analysis); 2) findings (how well presented data support findings, quality of findings); 3) use of methods to assess the respondents' perspectives and experiences.…”
Section: Study Quality Assessmentmentioning
confidence: 99%